NEIM-04. PROSPECTIVE STUDY OF SCREENING MRI OF THE BRAIN IN PATIENTS WITH METASTATIC OR INFLAMMATORY BREAST CANCER. (21st September 2021) - Aizer, Ayal; Catalano, Paul; Chen, Yu-Hui; Wickersham, Lacey; Gavrilovic, Alexandra; Lin, Nancy
Abstract: BACKGROUND: The management of brain metastases is often dictated by the size and number of lesions present, with more invasive/aggressive therapies such as resection and whole brain radiation utilized for more extensive intracranial disease. Consensus guidelines for patients with advanced lung cancer or melanoma recommend magnetic resonance imaging (MRI) of the brain to screen for brain metastases. Due to a lack of prospective studies demonstrating benefit, screening brain imaging is currently not recommended by consensus guidelines in breast cancer. APPROACH: Eligible patients are those with breast cancer initiating first-fourth line chemotherapy for extracranial metastatic disease or unresectable local recurrence devoid of prior intracranial involvement. A study-specific MRI (3D T1 pre-contrast + 3D T1 post-contrast acquisition) was developed to limit scan time to approximately 10-12 minutes. Patients with HR+/HER2- and HER2+ positive disease are randomized to screening brain MRIs vs not (primary outcome: neurologic quality of life, target N=156) while all patients with triple negative breast cancer (TNBC) receive brain MRIs (primary outcome: rate of symptomatic brain metastases relative to historical controls, target N=33). Screened patients undergo one MRI at enrollment and, if negative, a second MRI at first systemic progression. In addition, an exploratory cohort of patients with inflammatory breast cancer (IBC) managed with curative intent is included, in which patients undergo brain MRIs at baseline and, if negative, every six months for two years (primary endpoint: cumulative incidence of brain metastases, target N=25). In all cohorts, a multidisciplinary discussion is convened to determine optimal management in cases where brain metastases are identified. STUDY PROGRESS: The study activated in 2019. As of 7/9/21, 28 patients have been enrolled. Enrollment has been more robust in single arm cohorts (TNBC: 13/33 enrolled; IBC 8/25 enrolled) than in the randomized subset (7/156 enrolled). Updated accrual will be presented at the meeting.